2020
DOI: 10.3389/fneur.2020.545174
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Perfusion Effects of Cognitive Training and Transcranial Direct Current Stimulation in Mild-Moderate TBI

Abstract: Background: Persistent post-traumatic symptoms (PPS) after traumatic brain injury (TBI) can lead to significant chronic functional impairment. Pseudocontinuous arterial spin labeling (pCASL) has been used in multiple studies to explore changes in cerebral blood flow (CBF) that may result in acute and chronic TBI, and is a promising neuroimaging modality for assessing response to therapies. Methods: Twenty-four subjects with chronic mild-moderate TBI (mmTBI) were enrolled in a pilot study of 10 days of computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 88 publications
0
16
1
Order By: Relevance
“…That the finding is located in the right hemisphere, contralateral to the original site of stimulation, compared to the left DLPFC which received the highest presumed electric current density during tDCS but did not demonstrate connectivity change with any other region over time, also argues in favor of a compensation-recovery model, given the theorized role of the right hemisphere in depression, anxiety, and even somatization. Prior work by our group has found right DLPFC CBF reductions are associated with clinical improvement (Quinn et al, 2020) suggesting that recovery from prolonged postconcussive symptoms may be linked to regionally specific physiologic changes in the right prefrontal cortex characterized by both decreased connectivity and decreased perfusion. More work is needed to determine how functional connectivity between large-scale networks may underly chronic symptomatic states, compensation, and recovery after TBI, and to determine the strength of effects, optimal stimulation parameters, and mechanistic underpinnings of tDCS for mmTBI.…”
Section: Discussionmentioning
confidence: 85%
“…That the finding is located in the right hemisphere, contralateral to the original site of stimulation, compared to the left DLPFC which received the highest presumed electric current density during tDCS but did not demonstrate connectivity change with any other region over time, also argues in favor of a compensation-recovery model, given the theorized role of the right hemisphere in depression, anxiety, and even somatization. Prior work by our group has found right DLPFC CBF reductions are associated with clinical improvement (Quinn et al, 2020) suggesting that recovery from prolonged postconcussive symptoms may be linked to regionally specific physiologic changes in the right prefrontal cortex characterized by both decreased connectivity and decreased perfusion. More work is needed to determine how functional connectivity between large-scale networks may underly chronic symptomatic states, compensation, and recovery after TBI, and to determine the strength of effects, optimal stimulation parameters, and mechanistic underpinnings of tDCS for mmTBI.…”
Section: Discussionmentioning
confidence: 85%
“…Quinn, et al [ 71 ] investigated whether anodal tDCS over the left dorsolateral prefrontal cortex (DLPFC) plus cognitive training altered cerebral blood flow (CBF) on pseudocontinuous arterial spin-labeling (pCASL) sequences in mTBI patients. Twenty-four subjects (15 male) with chronic mTBI with cognitive persistent post-traumatic symptoms were enrolled in the study.…”
Section: Resultsmentioning
confidence: 99%
“…The frontal poles [ 64 ], DLFPC [ 71 ], and M1 [ 93 ] were the tDCS brain targets in the reviewed studies and the choice of the tDCS target brain target should coincide with the study outcomes and be relevant to the studied population. For example, the DLPFC is the important role that this site exerts in cognitive function and some studies have shown that DLPFC is associated with attention and working memory function [ 45 , 95 ].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to neuro-cognitive modulation, tDCS may invoke cerebroperfusional modulation associated with cortical hemodynamic functions (Zheng et al, 2011 ; Takai et al, 2016 ; Quinn et al, 2020 ). However, the interaction between tDCS induced effects on cognition and cerebral perfusion across aging remains widely unknown.…”
Section: Introductionmentioning
confidence: 99%